Need Analysis on Improving Reading Skills Using Interactive Kit Media Among Low Achievers - Ahmad, Noor Aini; Yin, Khoo Yin (International Journal of Psychosocial Rehabilitation, 2020)
This feasibility study intend to develop an interactive kit media to help low achievers in reading activites. Interactive kit media tools will be an appropriate learning tools to enhance reading skills among low achievers. 46 participants who teach reading skills to low achievers were selected through random sampling technique to answer the feasibility questionnaire. Findings show that there were no significant difference in requirements to develop interactive kit media for low achievers based on participants’ education levels with a value of [t = 2.64, p = .749 (p> .05)]. Ho1 indicates that low achievers need interactive kit media to learn reading skills. Findings also show that there were no significant difference in the content of interactive kit media by education levels with [t = -1.00, p = .752 (p> .05)]. This means that graduate and non-graduate teachers have the same opinion on the proposed interactive kit media and Ho2 was accepted. MANOVA results revealed a significant difference between participants’ education level with low achievers [F(1) = 6.98, p= 0.01(p< 0.05)] and interactive kit media [F (1) = 1.00, p = .323 (p> 0.05)], Pillai’s Trace [F(2, 43.0)=5.95, p<0.5]. In conclusion, there is a strong need to develop an interactive kit media learning tools to enhance reading skills among low achievers. This study recommends that low achievers need a better environment to learn reading skills and interactive kit media which consist of interactive games, augmented reality cards and e-book has a significant impact to improve their ability in accordance with Education 4.0.